IN VITRO CALLUS INDUCTION AND SHOOT REGENERATION IN ECLIPTA ALBA (L.) HASSK: Life Science-Botany - SHARMA, ARCHANA; SHIKHA BHANSALI; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2013)
Eclipta alba is a medicinal herb, also known as Bhringraj belonging to family Asteraceae. The plant has hepatoprotective, antimicrobial and hair growth promoting properties. The effect of various phytohormones on in-vitro callus induction and shoot regeneration in Eclipta alba from leaf explant was evaluated. The sterilized explants were inoculated on MS medium supplemented with different concentrations of auxins alone or in combination with cytokinins. Best result was observed on MS medium fortified with a combination of 2,4-D (1.0 mg/l) and BAP (0.5 mg/l). Shoot cultures were regenerated from the obtained callus on fresh MS medium containing BAP and NAA and its generation capacity, length and morphology were observed. Maximum number of shoots was obtained on a concentration of BAP (1.0 mg/l) and NAA (0.1 mg/l). In vitro generated callus and subsequent shoot proliferation can be used for large scale production of plant.